Aktivitas Metakognisi Mahasiswa Calon Guru Matematika dalam Pemecahan Masalah Terbuka - Usman Usman (Universitas Syiah Kuala, 2014)
This study aimed to describe the activities of pre-service teachers metacognition in problem solving algebra material's open. This study is a qualitative research. The subjects were pre-service students of the third semester of mathematics education courses at Syiah Kuala University. Techniques of data collection is done by open problem solving tests algebra and interview. Techniques of data analysis done by data reduction, data presentation and conclusion. From the analysis of the data obtained by the activity of pre-service teachers metacognition in mathematical problem solving algebra open material is: (1) the time to understand the problem, the subject realizes the importance of thinking about how to understand the problem, monitor, and evaluate the understanding of the problem, (2) the time to design the solution plan, the subject is aware of the importance of thinking about the steps plan, monitor, and evaluate the validity of the plan, (3) the time to implement the solution plan, subject aware of the importance of thinking, monitoring, and evaluating the implementation of solution plan, (4) the time to evaluate the results of the solution plan, subject aware of the importance of thinking about how to inspect, monitor and evaluate the results of the solution.